Potential for automated systems to monitor drying of agricultural products using optical scattering - Nagle, Marcus; Romano, G.B.; Udomkun, Patchimaporn; Argyropoulos, D.; Müller, J. (Springer, 2016)
Drying of agricultural products is a critical and energy-intensive processing step in the production of many foodstuffs. During convective drying, products are highly susceptible to thermal damage. In recent years, novel techniques have been established based on optical scattering due to the interaction of light with organic materials. The presented research investigated this approach using vis/NIR wavelengths to observe changes of quality parameters during drying of foodstuffs. The method was proven useful to monitor changes in moisture, color, and texture in a variety of products such as apple, mango, papaya, litchi, and bell pepper. Although many applications have been confirmed, additional hardware and software aspects still need to be refined. Optical scattering shows strong potential for implementation as a nondestructive method for in-line control of product qualities during industrial drying processes. A robotic prototype should be developed that is capable of automated measurement of agricultural products during drying. Optimization of product quality and prevention of energy waste by over-drying are among the potential impacts of the developed technology.